Kingdom of the Netherlands : Netherlands. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes the wage moderation in the Netherlands. Wage growth has been subdued in the Netherlands despite tighter labor market conditions in recent years. Besides various cyclical factors, rising labor market flexibility may have contributed to the wage moderation in the Netherlands. Like other advanced economies, slower productivity growth and lower expected inflation are important drivers to the wage moderation in the recent years. In addition to that, remaining slack in the labor market also weighed on wage growth. Going forward, wages are expected to grow faster given higher expected inflation, foreign wage spillovers, and tightening labor market.